2021
DOI: 10.3389/fpsyg.2021.670223
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Interpersonal Sensitivity on Smartphone Addiction: A Moderated Mediation Model

Abstract: Smartphone addiction is a behavioral dependence characterized by excessive or compulsive Internet use and a preoccupation with and loss of control over this use that interferes with an individual’s daily functioning and results in negative mental processes and subsequent social consequences. Smartphone addiction can negatively impact physical and mental health as well as academic performance, sleep quality, and even interpersonal interaction and relationships. Based on the compensatory Internet use theory, thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 38 publications
1
18
0
Order By: Relevance
“…Research has discovered that a high quality of peer relationships benefits the mental health of adolescents (25). The study among Chinese college students indicated that interpersonal sensitivity positively relates to negative emotions (26) and contributes to individuals' mobile phone addictions (27), which could predict depression (28). Nonetheless, only a few explorations about the relationship between interpersonal sensitivity and depression among Chinese college freshmen have been conducted.…”
Section: Introductionmentioning
confidence: 99%
“…Research has discovered that a high quality of peer relationships benefits the mental health of adolescents (25). The study among Chinese college students indicated that interpersonal sensitivity positively relates to negative emotions (26) and contributes to individuals' mobile phone addictions (27), which could predict depression (28). Nonetheless, only a few explorations about the relationship between interpersonal sensitivity and depression among Chinese college freshmen have been conducted.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, in their research on private university students in Lebanon, Hawi and Samaha ( 34 ) found that only independent self-construal was a significant and negative predictor of PSMU. However, as a personality trait, self-construal has been explored only with PSMU, but has not been widely considered in relation to its association with PSU ( 35 ). Therefore, investigating whether or not self-construal affects PSU is one of the objectives of the present paper.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the extant literature has demonstrated that FoMO can mediate psychological variables (i.e., depression, envy) and PSU ( 3 , 41 ). A survey study also found that FoMO and relational (interdependent) self-construal had a moderated mediation effect on the relationship between smartphone addiction and interpersonal sensitivity (i.e., a personality tendency characterized by constantly worrying about negative social evaluation) ( 35 ). Although FoMO has been conceptualized in the framework of the self-determination theory ( 36 ), the relationship between self-construal and FoMO is still unclear.…”
Section: Introductionmentioning
confidence: 99%
“…On the one hand, FOMO has for instance been associated with development of problematic usage of a number of internet applications, including problematic internet usage (Röttinger et al, 2021) and smartphone addiction (Alinejad, Parizad, Yarmohammadi, & Radfar, 2022). However, on the other hand, an increasing number of studies underscore the role of social and self-related cognitions in this association such that the association between FOMO and smartphone addiction is mediated by loneliness (Alinejad et al, 2022) while FOMO mediates the association between parental support, self-construal, self-concept clarity or interpersonal sensitivity with problematic smartphone use (Kim, 2022; Lin et al, 2021; Servidio, Sinatra, Griffiths, & Monacis, 2021).…”
Section: Discussionmentioning
confidence: 99%